HUBUNGAN WORKING MEMORY DAN LITERACY DENGAN KEMAMPUAN PRAGMATIK ANAK USIA PRASEKOLAH DI SURAKARTA - Putra, Sinar Perdana; Muryanti, Muryanti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The ability to carry out good social interactions in children must be accompanied by good cognitive abilities as well. Cognitive is related to intelligence. Memory is complex and central to many cognitive operations. Working Memory (WM) is the ability to store information and process information at the same time. There is a strong relationship between Working Memory (WM) and Literacy abilities. Literacy is generally defined as the ability to read and write and use spoken language. Research Objective: To determine the relationship between working memory and literacy with the pragmatic abilities of preschool children in Surakarta. Subjects and Methods: This study used a correlational design. The sample size for this study was 173 children. Data collection uses questionnaires and test instruments. Research Results: Hypothetical testing using the Simultaneous Test can be explained that the variables working memory ability and literacy ability are jointly related to the pragmatic abilities of preschool aged children in Surakarta with a significance figure of 0.000. The resulting coefficient of determination (R2) is 0.079 or 7.9%. In the multiple linear regression test, the equation Y = 48,714 + 1,740 X1 is obtained.